Calcium Binding by Synaptotagmin's C2A Domain is an Essential Element of the Electrostatic Switch That Triggers Synchronous Synaptic Transmission. - Striegel, A.R.; Biela, L.M.; Evans, C.S.; Wang, Z.; Delehoy, J.B.; Sutton, R.B.; Chapman, E.R.; Reist, N.E. (Journal of Neuroscience, 2012)
Synaptotagmin is the major calcium sensor for fast synaptic transmission that requires the synchronous fusion of synaptic vesicles. Synaptotagmin contains two calcium-binding domains: C2A and C2B. Mutation of a positively charged residue (R233Q in rat) showed that Ca2+-dependent interactions between the C2A domain and membranes play a role in the electrostatic switch that initiates fusion. Surprisingly, aspartate-to-asparagine mutations in C2A that inhibit Ca2+ binding support efficient synaptic transmission, suggesting that Ca2+ binding by C2A is not required for triggering synchronous fusion. Based on a structural analysis, we generated a novel mutation of a single Ca2+-binding residue in C2A (D229E in Drosophila) that inhibited Ca2+ binding but maintained the negative charge of the pocket. This C2A aspartate-to-glutamate mutation resulted in ?80% decrease in synchronous transmitter release and a decrease in the apparent Ca2+ affinity of release. Previous aspartate-to-asparagine mutations in C2A partially mimicked Ca2+ binding by decreasing the negative charge of the pocket. We now show that the major function of Ca2+ binding to C2A is to neutralize the negative charge of the pocket, thereby unleashing the fusion-stimulating activity of synaptotagmin. Our results demonstrate that Ca2+ binding by C2A is a critical component of the electrostatic switch that triggers synchronous fusion. Thus, Ca2+ binding by C2B is necessary and sufficient to regulate the precise timing required for coupling vesicle fusion to Ca2+ influx, but Ca2+ binding by both C2 domains is required to flip the electrostatic switch that triggers efficient synchronous synaptic transmission.